Quantitative and Qualitative Difference in Antibody Response against Omicron and Ancestral SARS-CoV-2 after Third and Fourth Vaccination - Sascha Hein; Ines Mhedhbi; Tobias Zahn; Catarina Sabino; Nuka Ivalu Benz; Younes Husria; Patricia Maria Renelt; Floriane Braun; Doris Oberle; Thorsten J. Maier; Christoph Hildt; Eberhard Hildt (Vaccines, 2022)
Waning immunity against SARS-CoV-2 and the emergence of variants, especially of the most distant variant, Omicron, affect titers of neutralizing antibodies in the sera of vaccinated individuals. Thus, two vaccinations with the mRNA vaccine BNT162b fail to induce neutralizing antibodies against the Omicron variant. A first booster vaccination increases Omicron-RBD-binding IgG and IgA and neutralizing capacity. In comparison, the Wuhan isolate titers of the Omicron variant binding antibodies are 8.5 lower. After a third vaccination, induction of Omicron-RBD- and Wuhan-RBD-binding antibodies follows the same kinetic. Five to six months after the third vaccination, there are still Omicron-RBD-binding antibodies detectable, but 35.9 percent of the analyzed sera fail to neutralize the Omicron variant, while all sera efficiently neutralize the Delta isolate. In the case of the Wuhan-RBD, a significantly larger number of stable antigen–antibody complexes is formed than in Omicron-RBD. A fourth vaccination with mRNA-1273 temporarily restores levels of Omicron-, Delta- and Wuhan-specific antibodies. Comparing different booster strategies revealed that the breadth of the immune response is not affected by the vaccination regimen. Taken together, these data indicate that booster vaccinations (third and fourth dose) increase the breadth of the immune response, but there is a qualitative difference of antibodies with respect to the stability of antigen–antibody complexes and persistence of antibody titers.